0316 Actigraphy-Derived Sleep Health Profiles and Mortality in Older Men and Women. (25th May 2022) - Wallace, Meredith; Lee, Soomi; Stone, Katie; Hall, Martica; Smagula, Stephen; Redline, Susan; Ensrud, Kristine; Ancoli-Israel, Sonia; Buysse, Daniel
Abstract: Introduction: To identify actigraphy sleep health profiles in older men (Osteoporotic Fractures in Men Study; N=2, 640) and women (Study of Osteoporotic Fractures; N=2.430), and to determine whether the identified profiles predict mortality. Methods: We applied a novel and flexible clustering approach (Multiple Coalesced Generalized Hyperbolic mixture modeling) to identify sleep health profiles based on actigraphy midpoint timing, midpoint variability, sleep interval length, continuity, and napping/inactivity. Adjusted Cox models were used to determine whether profile membership predicts time to all-cause mortality. Results: We identified similar profiles with different prevalences in men and women: High Sleep Propensity [HSP] (20% of women; 39% of men; high napping and high continuity); Adequate Sleep [AS] (74% of women; 31% of men; average actigraphy levels); and Abnormal Continuity/Timing [ACT] (6% of women; 30% of men; low continuity and late/variable midpoint). In women, ACT was associated with increased mortality risk (Hazard Ratio [HR]=1.59 for ACT vs. AS; 1.75 for IS vs. HSP). In men, ACT and AS were associated with increased mortality risk relative to HSP (1.19 for IS vs. HSP; 1.22 for AS vs. HSP). Conclusion: These findings suggest several considerations for sleep-related interventions in older adults. For instance, interventions may be developed to target the combination of low continuity with late/variable midpoint. Findings also indicate that high napping/inactivity co-occurs with high sleep continuity in some older adults. Although high napping/inactivity is typically considered a risk factor for deleterious health outcomes, our findings suggest that it may not be inherently problematic when occurring in combination with high sleep continuity. Support (If Any): The Osteoporotic Fractures in Men (MrOS) Study is supported by NIH grants U01 AG027810, U01 AG042124, U01 AG042139, U01 AG042140, U01 AG042143, U01 AG042145, U01 AG042168, U01 AR066160, UL1 TR000128, R01 HL071194, R01 HL070848, R01 HL070847, R01 HL070842, R01 HL070841, R01 HL070837, R01 HL070838, and R01 HL070839. The Study of Osteoporotic Fractures (SOF) is supported by NIH grants R01 AG005407, R01 AR35582, R01 AR35583, R01 AR35584, R01 AG005394, R01 AG027574, R01 AG027576, and R01 AG026720. This study is also supported by NIH grants R01AG056331 and RF1AG056331 (PI: Wallace), R56AG065251 (PI: Lee), K01MH112683 (PI: Smagula), and R35HL135815 (PI: Redline).